2018
DOI: 10.1016/s2213-2600(18)30288-1
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive versus symptom-guided drainage of malignant pleural effusion via indwelling pleural catheters (AMPLE-2): an open-label randomised trial

Abstract: Cancer Council of Western Australia and the Sir Charles Gairdner Research Advisory Group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 25 publications
3
121
1
4
Order By: Relevance
“…Very often, the lung may appear non‐expandable immediately after evacuation of MPE but will expand fully over a few days, especially if the effusion has accumulated over a long period of time. In the Australasian Malignant PLeural Effusion trial‐2, patients with NEL could develop autopleurodesis especially if drained daily via an indwelling pleural catheter (IPC). Clinicians must also discard the old belief that patients with NEL will not derive symptom benefits from fluid drainage (reviewed elsewhere) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very often, the lung may appear non‐expandable immediately after evacuation of MPE but will expand fully over a few days, especially if the effusion has accumulated over a long period of time. In the Australasian Malignant PLeural Effusion trial‐2, patients with NEL could develop autopleurodesis especially if drained daily via an indwelling pleural catheter (IPC). Clinicians must also discard the old belief that patients with NEL will not derive symptom benefits from fluid drainage (reviewed elsewhere) …”
mentioning
confidence: 99%
“…Martin et al 2 defined NEL as apposition of the lung to <50% of the lateral chest wall on chest radiographs (CXR), although other studies used more stringent cut-off values (<25%). 7 NEL from malignant causes are often not uniformly trapped. Two-dimensional images (e.g.…”
mentioning
confidence: 99%
“…However, this statement was not designed to be a precise diagnostic criterion for NEL and other studies have used alternatives (e.g. <75% pleural apposition) . A different definition of NEL might improve inter‐observer variability, but may be less clinically relevant as subtle NEL might still be amenable to a pleurodesis attempt.…”
Section: Discussionmentioning
confidence: 99%
“…<75% pleural apposition). 3,11,12 A different definition of NEL might improve inter-observer variability, but may be less clinically relevant as subtle NEL might still be amenable to a pleurodesis attempt.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPLE (Australasian Malignant PLeural Effusion) RCT found that IPC, compared to talc pleurodesis, significantly reduces number of days MPE patients spent in hospital in their remaining life as well as need of further invasive pleural procedures . Both the ASAP and AMPLE‐2 RCTs showed that daily drainage after IPC insertion promotes spontaneous pleurodesis and likelihood of catheter removal . Complications associated with IPC use are generally acceptable .…”
Section: Acknowledgementsmentioning
confidence: 99%